(3GdQjGVjGJ hGdJMdjd GdYOOjs - (3UaGA Ydi(B, (3fGUQs ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B,s, 2008)
(3jVe fXQjI GdeLehYGJ hWQb GdYO, GdeJLgGJ hGdeUahaGJ hGdeMOOGJ, GdJaGVd hGdJcGed ,GdJSdSdGJ ZjQ GdeJfGgjI, GdeYGOdGJ GdJaGVdjI ef GdeQJHI GdGhdi, GdJMdjd GdYOOj, Md GdeYGOdGJ GdNWjI hGddGNWjI, GdJaGVd hGdJcGed GdYOOj, GdMdhd GdYOOjI ddeYGOdGJ GdJaGVdjIs
(3GdeQGLY U(B.367s
Keywords: (3GdJaGVd hGdJcGeds; (3GdQjGVjGJs; (3GdQjGVjGJ(B- (3GdJMdjd GdYOOjs